2009
DOI: 10.1007/s11267-009-9227-9
|View full text |Cite
|
Sign up to set email alerts
|

Submerged Membrane System with Biofilter as a Treatment to Rainwater

Abstract: Rainwater has been used as drinking water in Thailand for centuries especially in the rural parts and is accepted as an important water resource. From past to present, the quality of rainwater has changed with the land use of the landscape and its water quality is influenced by a diverse range of conditions such as the management of pollutant sources, the catchment condition, wind and meteorological conditions and the location of rainwater collection points. In this study, the quality of rainwater collected of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As with surface water, rainwater can be contaminated with coarse and fine particulate matters, chemicals, microorganisms, metals, and ionic elements, which may be detrimental health effects [ 76 , 77 ]. Previous studies have suggested that the human health consequences associated with rainwater are low in intensity and are linked to the type of rainwater harvesting systems design and maintenance [ 64 , 78 ].…”
Section: Contamination Of Rainwater and Quality Assessmentmentioning
confidence: 99%
“…As with surface water, rainwater can be contaminated with coarse and fine particulate matters, chemicals, microorganisms, metals, and ionic elements, which may be detrimental health effects [ 76 , 77 ]. Previous studies have suggested that the human health consequences associated with rainwater are low in intensity and are linked to the type of rainwater harvesting systems design and maintenance [ 64 , 78 ].…”
Section: Contamination Of Rainwater and Quality Assessmentmentioning
confidence: 99%
“…However, this process had a marginal impact in reducing total heterotrophic bacteria. Activated carbon treatment based on membrane filtration to remove dissolved organic solids (DOCs) demonstrated limited contaminants removal efficiency [15]. For example, the use of antimicrobial silver ions in combination with settling tanks and conventional filtration was investigated by Adler et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of oxygen or nitrate in recharge water can stimulate bacteria and produce iron or manganese oxides and hydroxide precipitates [8]. The stormwater quality data extracted from the literature (Table 1) show that iron is the most common metal pollutant in stormwater [6,[9][10][11][12][13][14], and the iron content ranges from 0.3 to 1.8 mg/L, generally exceeding the Australian Drinking Water Guidelines(AWDG) [15] standard. The total iron concentration specified in the water quality standard for reclaimed water recharge in China (GB/T 19772-2005) stipulates that the limit value of the total iron concentration is 0.3 mg/L; in Beijing, it is 0.3-1.0 mg/L [14]; for most states in America, it is 0.3 mg/L [16,17]; and in the former Soviet Union, it is 3 mg/L [18].…”
Section: Introductionmentioning
confidence: 99%